Ketahanan Gambut Terstabilisasi Semen Dan Kapur Terhadap Kebakaran Menggunakan Pendekatan Variasi Kadar Air - Juliasman, Rendy Dwi; Muhardi, Muhardi; Wibisono, Gunawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A peatland is an area with naturally accumulated decayed organic materials (peat) at the surface. Riau Province has the largest peatlands in Sumatra i.e. 56.1% from the total peatlands in Sumatra. Peat fires have been many times occurred in Indonesia. Stabilization proven to preverent peat fire in Malaysia. Most common available stabilization materials are cement and lime. Research conducted by Zamzam (2017) showed that peat mixed with 5% lime and 15% cement at 100% moisture content, could increase its strength and became less combustible. This research attempts to correlate the mechanical properties of peat that stabilized with cement and lime at various water contents, and its burning resistance. Several water contents applied were 51.52%, 76.77%, 81.82%, 102.02%, 107.07%, and 112.12%. The burning tests were not conducted on sample of 51,52 % water content. The result showed that the optimum strength of stabilized peat mixtures achieved at water content of 76,77%, which had UCS and soaked CBR value of 97.35 kPa and 16,23%, respectively. The burning test showed that the higher the water content, the delay combustible the peat sample,however the mechanical test and burning tests showed the opposite results.Keywords: peat fire, cement, lime, CBR, and UCS.